2014
DOI: 10.1093/ejcts/ezu043
|View full text |Cite
|
Sign up to set email alerts
|

Pericardial fat is strongly associated with atrial fibrillation after coronary artery bypass graft surgery†

Abstract: PFV is strongly associated with AF following CABG, independently of many traditional risk factors. Our findings suggest that PFV may represent a novel risk factor for postoperative AF. However, the role of pericardial fat in AF mechanism needs to be further delineated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…This corresponds well with our findings, not only confirming the independent relationship between postoperative AF and EAT volume, but also extending prior observations to the role of regional EAT located around the LA in the onset of postoperative AF. Of note, the study of Drossos et al was limited to application of 4-slice computed tomographic scanner and examination of only a single CCTA parameter rather than performance of a comprehensive CCTA analysis [12]. Thus, only our report introduces noninvasive CCTA as a potential gatekeeper for refined AF risk stratification, as depicted by the ROC analysis showing good negative predictive value of the LA EAT volume >3.4 ml for exclusion of postoperative AF.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…This corresponds well with our findings, not only confirming the independent relationship between postoperative AF and EAT volume, but also extending prior observations to the role of regional EAT located around the LA in the onset of postoperative AF. Of note, the study of Drossos et al was limited to application of 4-slice computed tomographic scanner and examination of only a single CCTA parameter rather than performance of a comprehensive CCTA analysis [12]. Thus, only our report introduces noninvasive CCTA as a potential gatekeeper for refined AF risk stratification, as depicted by the ROC analysis showing good negative predictive value of the LA EAT volume >3.4 ml for exclusion of postoperative AF.…”
Section: Discussionmentioning
confidence: 79%
“…CCTA has been introduced as a useful noninvasive tool that demonstrates high performance for assessing the anatomical features of PVs and LA, and has been successfully employed in the planning of ablation procedures [6,17]. In the only study assessing the potential application of CCTA for prediction of AF after CABG, Drossos et al reported the total volume of EAT surrounding the entire heart to be independently associated with postoperative AF [12]. This corresponds well with our findings, not only confirming the independent relationship between postoperative AF and EAT volume, but also extending prior observations to the role of regional EAT located around the LA in the onset of postoperative AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EAT is metabolically active tissue and is thought to be a source of inflammatory cytokines. Several tomographic studies have shown that EAT volume is associated with cardiac arrhythmias, especially the development of AF in surgical and non-surgical patients (8,9). Al Chekakie et al (14) suggested that EAT volume is a strong independent factor aside from traditional risk factors in the development of paroxysmal and persistent AF.…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial adipose tissue (EAT) and the myocardium are not separated by fascia, and therefore share the same microcirculation. EAT is an active tissue with inflammatory and endocrine features, and it plays a crucial role in the pathogenesis of cardiac arrhythmias (8,9). Red blood cell distribution width (RDW), or anisocytosis, is an indicator of variability in the size of erythrocytes.…”
Section: Introductionmentioning
confidence: 99%